Tinjauan Kelayakan Bisnis Syariah Pada Usaha Sarang Burung Walet Di Dusun Batri Desa Kaballangang - Reza Syaripuddin; Mustamin B; Rasyidah Bulqis (STAI DDI Pinrang, 2024)
This research is titled “A Study of the Feasibility of a Sharia Business in the Edible Bird’s Nest Enterprise in Batri Hamlet, KaballangangnVillage.” The main objective of this research is to analyze the feasibility of the edible bird’s nest business from a sharia business perspective by considering legal, market, management, and environmental aspects.The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The findings of the first research question indicate that the swiftlet nest business in Batri Hamlet, Kaballangang Village, has significant economic potential, but there are challenges such as price fluctuations. From the perspective of Sharia law, this business is permissible as long as it adheres to Islamic principles, such as justice and transparency.The findings of the second research question indicate that the swiftlet nest business in Batri Hamlet, Kaballangang Village, is running well and has the potential to improve family economies. This is due to the relatively high price of swiftlet nests and the satisfactory harvests obtained by swiftlet entrepreneurs. In conclusion, this business is feasible under sharia principles but requires improvements in certain aspects to better align with Islamic economic principles and sustainability.